Adolescence and youths in Tunja (2011)
This research paper examines the policies regarding young people in Colombia, and contrasts them with the actions and realities tracked in the city of Tunja over the last few years. The Colombian government has created policies focused on generating auspicious conditions and environments for young people, which have been carried out with minimal operational impact, however, the previous years have been notable for their reflection on the theme of adolescence and youths. Prevention campaigns and agreements have been created in Tunja, in order to offset problems created by the consumption of alcohol, drug addiction and youth culture, however, according to a preliminary survey in educative institutions, there is still evidence of a lack of awareness of youth culture and the laws which support it.